2010
DOI: 10.1039/b927019a
|View full text |Cite
|
Sign up to set email alerts
|

Mapping hydrophobicity at the nanoscale: Applications to heterogeneous surfaces and proteins

Abstract: Approaches to quantify wetting at the macroscale do not translate to the nanoscale, highlighting the need for new methods for characterizing hydrophobicity at the small scale. We use extensive molecular simulations to study the hydration of homo and heterogeneous self-assembled monolayers (SAMs) and of protein surfaces. For homogeneous SAMs, new pressure-dependent analysis shows that water displays higher compressibility and enhanced density fluctuations near hydrophobic surfaces, which are gradually quenched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
279
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(306 citation statements)
references
References 58 publications
27
279
0
Order By: Relevance
“…Recent molecular simulations have suggested that single-molecule interactions can potentially identify nanoscale differences in hydrophobicity 22 . Here, we use a photo-patterned hydrophobically modified surface 23 as a model system to prepare spatially well-defined areas of varying hydrophobicity, and a fluorescently labelled fatty acid (BODIPY-labelled dodecanoic acid) as a probe molecule.…”
Section: Resultsmentioning
confidence: 99%
“…Recent molecular simulations have suggested that single-molecule interactions can potentially identify nanoscale differences in hydrophobicity 22 . Here, we use a photo-patterned hydrophobically modified surface 23 as a model system to prepare spatially well-defined areas of varying hydrophobicity, and a fluorescently labelled fatty acid (BODIPY-labelled dodecanoic acid) as a probe molecule.…”
Section: Resultsmentioning
confidence: 99%
“…On the GRA-2H and the BN-2H defects, the OH group of the dissociated water molecule can act both as a donor and an acceptor, leading to stronger interactions with the liquid film. [57][58][59] For instance the GRA-2H defect accepts ca. 1.1 bonds and donates ca.…”
mentioning
confidence: 99%
“…The contribution of the hydrophobic amino acids becomes more important as the patch size increases. The polar amino acids expose an approximately constant fraction of their non-polar area independent of patch size [30]. Though the mobility of residues on the surface is generally higher, it decreases for the polar residues with increasing patch size [31].…”
Section: International Journal Ofmentioning
confidence: 98%